PENGARUH INDONESIA-EUROPE CEPA (COMPEHERENSIVE ECONOMIC PARTNERSHIP AGREEMENT) TERHADAP PENURUNAN EKSPOR TEKSTIL INDONESIA KE ITALIA TAHUN 2014-2017 - Zein, Fikri Falah; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The research analyzes The I-EU CEPA (Compeherensive Economic Partnership Agreement) Towards The Decreased of Textile Export Indonesian’s to Italy. extile Products is one of the mainstay in Indonesian Export commodities. Indonesia is targeting EU market, one of them is Italy. The Indonesian government is working hard to reach an agreement I-EU CEPA that has reached the fourth stage of negotiations. If this cooperation reach an agreement as desired by the Indonesian side, then Indonesia has a great chance to dominate the EU market.The research teoritically has been built by using Liberalism perspective. The kind of this research is qualitative research. The data is based on secunder data through literature study such as book,website, and each other.The final result of this research is not yet reached agreement between Indonesia and EU related trade agreement of CEPA have an effect on to decrease value of Export of Textile and Textile Product Indonesia to Italy. The talks are reaching the fourth round. The EU deliberately draws the outcome of this agreement, if Indonesia gains freedom of trade then Indonesia will dominate the EU market. Indonesian government. It is expected that this agreement will be reached so that the value of Indonesian textile exports will increase again.Keywords: Textile and Textile Products, Agreement, Indonesia EU CEPA